27‐3 2‐D Confinement of LCs with Virtual Walls for a Fast Response LCD. Issue 1 (May 2017) - Choi, Tae-Hoon; Woo, Jae-Hyeon; Choi, Yeongyu; Oh, Seung-Won; Yoon, Tae-Hoon
Abstract : We report a simple method for reducing the response time of homogeneously aligned liquid crystal (LC) cells by using two‐dimensional confinement of the LCs. We have shown that the switching speed can be increased by serval fold in in‐plane switching and fringe‐field switching cells by introducing interdigitated electrodes parallel to the LC alignment direction. We also report an interdigitated pixel electrode structure with alternating tilts for a much wider viewing angle by aligning the LCs without a pretilt. In addition to a short response time and wide viewing angle, this device allows a much larger deviation of the LC alignment direction which is essential for mass production. Moreover, LCs with negative dielectric anisotropy can be used to minimize the transmittance decrease.